Physical regularities in the cracking of nanocoatings and a method for an automated determination of the crack-network parameters - Maruščak, P. O. (Materiali in tehnologije, 2012)
The regularities and spatial distribution of multiple cracking of a nanocoating are investigated. It is found that in the cracking zones the relaxation of the stresses accumulated in the coating takes place; moreover, the intensity of its failure is determined by the structural level of defect accumulation. A new algorithm for a digital identification of the elements of a crack network in a nanocoating is proposed, and its adequacy is checked.
Keywords: nanocoatings; nanoprevleke; cracks; razpoke; materials testing; preiskava materiala